2022
DOI: 10.1155/2022/5181241
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood-Derived Mesenchymal Stem Cells Modulate Macrophage Plasticity through the IL-10/STAT3 Pathway

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells that can skew the balance of M1/M2 macrophage polarization towards the M2 phenotype via their paracrine effects, thereby promoting anatomical and functional recovery after many inflammatory diseases induced by macrophages. However, the underlying mechanism is still poorly understood. This study focused on the IL-10/STAT3 pathway and investigated whether IL-10 secreted by PBMSCs could mediate M2 polarization through the activation of this pathway. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Expression of pro-inflammatory mediators like cell surface receptors, chemokines, and cytokines is inhibited by the anti-inflammatory factor IL-10 ( 56 ). Additionally, research conducted by our team has demonstrated that co-culturing peripheral blood mesenchymal stem cells with macrophages can encourage the polarization of macrophages toward M2 type via the IL-10/JAK/STAT3 pathway, as well as reduce the expression and secretion of pro-inflammatory factors while increasing the expression and secretion of anti-inflammatory ones ( 57 ). In studies of enterohepatic crosstalk in nonalcoholic steatohepatitis, it has also been demonstrated that activation of this pathway promotes M2-type macrophage polarization, which ultimately attenuates the intensity of inflammation in intestinal tissues and maintains intestinal homeostasis ( 58 ).…”
Section: Research On the Signaling Pathways Related To Stat3 Regulati...mentioning
confidence: 99%
“…Expression of pro-inflammatory mediators like cell surface receptors, chemokines, and cytokines is inhibited by the anti-inflammatory factor IL-10 ( 56 ). Additionally, research conducted by our team has demonstrated that co-culturing peripheral blood mesenchymal stem cells with macrophages can encourage the polarization of macrophages toward M2 type via the IL-10/JAK/STAT3 pathway, as well as reduce the expression and secretion of pro-inflammatory factors while increasing the expression and secretion of anti-inflammatory ones ( 57 ). In studies of enterohepatic crosstalk in nonalcoholic steatohepatitis, it has also been demonstrated that activation of this pathway promotes M2-type macrophage polarization, which ultimately attenuates the intensity of inflammation in intestinal tissues and maintains intestinal homeostasis ( 58 ).…”
Section: Research On the Signaling Pathways Related To Stat3 Regulati...mentioning
confidence: 99%
“…On the other hand, in this study, we also determined that IL-10 levels were significantly reduced after WCP treatment. IL-10 is an anti-inflammatory cytokine [44]. Elevated levels of IL-10 were reported to promote tumor development [45].…”
Section: Discussionmentioning
confidence: 99%
“…To counteract the sustained inflammatory response and tissue damage produced by M1 macrophages, the body induces M2 macrophage polarization by activating Th2 cells to release IL-4 and IL-13 and binding IL-4R [ 33 ]. Furthermore, IL-10 can control M2 macrophage activity by stimulating the downstream STAT3 signaling pathway [ 34 ]. M2 macrophages secrete anti-inflammatory factors that antagonize the chronic inflammatory response induced by M1 macrophages; in addition, M2 macrophages have a strong phagocytic capacity to remove debris and apoptotic cells and suppress inflammation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%